Place Based Policies with Unemployment - Kline, Patrick; Moretti, Enrico (American Economic Review, 2013)
We develop a stylized model of frictional local labor markets with the goal of studying the efficiency of unemployment differences across areas. The model adapts the widely used Diamond-Mortensen-Pissarides framework to a local labor market setting with a competitive housing market. The result is a simple search analogue of the classic Roback model that provides a tractable environment for studying the effects of local job creation efforts.